Immunohistochemical expression of SPARC is correlated with recurrence, survival and malignant potential in meningiomas - BOZKURT, SÜHEYLA (WILEY, 2009)
Meningioma is a common neoplasm that constitutes almost 30% of all primary central nervous system tumors and is associated with inconsistent clinical outcomes. The extracellular matrix proteins play a crucial role in meningioma cell biology and are important in tumor cell invasion and in progression to malignancy. SPARC (secreted protein, acidic and rich in cysteine) (osteonectin) is a matricellular glycoprotein that regulates cell function by interacting with different extracellular matrix proteins. The aim of this study was to evaluate the expression of SPARC with proliferation index, p53 reactivity in WHO grade 1 (benign), grade 2 (atypical) and grade 3 (anaplastic) meningiomas and correlate with clinical features of the patients, including location of the tumor, recurrence of the tumor and survival of patients. We studied 111 meningiomas, 69 being benign, 34 being atypical and eight being anaplastic meningiomas of various histological types. Using immunohistochemical analysis, we evaluated the expression of SPARC, Ki-67 (MIB-1) and p53 in meningiomas. Immunohistochemical scores of SPARC were determined as the sum of frequency (0-3) and intensity (0-3) of immunolabeling of the tumor cells. A high immunohistochemical score (4-6) for SPARC was more frequent in atypical and in anaplastic meningiomas than in benign meningiomas (p < 0.01). MIB-1 proliferation index showed significant association between tumor grades in meningiomas (p < 0.01). At the end of a follow-up period of 47.53 +/- 25.04 months, 30 tumors recurred. A high SPARC expression was significantly associated with tumor recurrence (p = 0.02). The immunoreactivity of p53 protein and MIB-1 score were significantly higher in recurrent meningiomas than in non-recurrent meningiomas. The cumulative survival of patients with high SPARC expression was significantly lower than patients with low SPARC expression. The high SPARC expression scores were predominantly identified in meningothelial, fibrous and chordoid meningiomas; low SPARC expression scores were mostly spotted in secretory and psammomatous meningiomas. Evaluating SPARC expression might help assessing recurrence risk and survival estimation in meningiomas.
Keywords: Meningioma; recurrence; SPARC; osteonectin; MIB-1 index; p53; MATRICELLULAR PROTEIN SPARC; NEOPLASTIC PROGRESSION; GENE-EXPRESSION; CYSTEINE SPARC; CANCER; TUMOR; RICH; SPARC/OSTEONECTIN; CARCINOMA; OSTEONECTIN/SPARC